STUDY OF THE EFFECT OF ADDITIONAL VARIATIONS IN LAWELE ASBUTON AND ASPHALT PEN 60/70 LEVEL IN THE UTILIZATION OF Limestone AS A RUDE AGGREGATE TO STABILITY AND AC-WC MIXED DURABILITY - Lambang Basri Said; Mysdelty (Moeslim Indonesian University (UMI), 2018)
Bitumen Asbuton as a type of natural asphalt extracted from which there are many deposits in Indonesia is an alternative that can be used to improve the performance of asphalt mixtures where asphalt concrete pavements often experience problems, namely not achieving the design life due to early damage and at the same time it is expected to be able to utilize materials local. The purpose of this study was to obtain the results of the optimization of the asphalt mixture asphalt Laston Lapis Aus (AC-WC) when used Asphalt Oil and the addition of Asbuton which varied 0%, 5%, 7% and 10% and to obtain the characteristics of the asphalt mixture asphalt mixture (AC) -WC) which uses limestone as coarse aggregate. The research procedure uses the experimental method by referring to the provisions, terms and procedures of SNI, Bina Marga, AASHTO, or other related organizations. Sources of data obtained from research results as primary data and secondary data obtained from other sources which are the results of research that has been done previously. For the mixture with the addition of Asbuton 0%, 5%,7% and 10%, the optimum value of asphalt content (KAO) is 6.2%. The stability values ​​are 2161 kg, 2257 kg, 2410 kg and 2371 kg. The VIM score is 4.26%; 4.69%; 4.82%; and 5.10%. The deformation values ​​are 1.4825 (0%) and 0.945 (7%). With the addition of Asbuton will increase the value of stability, and the value of VIM also increases and reduces the rate of deformation. A mixture that uses asbuton a lot shows a greater stability value and is more resistant to hot temperatures and reduces the rate of deformation of the mixture so that it is indicated that it can improve the performance of the mixture and increase the durability of the mixture.